Plan de mejoramiento hotel Hacienda Combia ubicado en Calarcá, Quindío (2013)
Hacienda Hotel COMBIA located at km 3 route Calarcá - Barcelona which was carried out on the improvement plan, which is defined as a control element, which allows the continuous improvement and accomplishment of the institutional goals with corporate order, thus allowing to fulfill its Mission, in relation to the Action Plan, this model provides a framework reference that the management of the Hotel Hacienda Combia, will establish parameters of processes which are handled by the administrative area; especially of marketing for decision-making in critical situations. For the globalized world in which we are, it is paramount present frequently guidelines of improvement, in such way guarantee quality, good service and good administrative management of the business processes to be self-sustaining and profitable, so in each and every one of the small and medium enterprises this since the capital, labor and future of people with a desire to succeed and support the development of society. In the present investigation was designed a Improvement Plan, which ultimately led to the improvement of processes and financial performance of the company under study. This was done by analyzing the technical flaws and problems, all structured in the Basic Model Strategic Management (Environmental Analysis, Strategy Formulation, Implementation and Evaluation Strategy and Control), which receives a qualitative and global observation the company, and by the Matrix Model for Management Modernization Organizations, was obtained quantitative and measurable results, deepened in the proper choice of a functional strategy for the hotel, which drives business development and makes the Hotel Hacienda Combia in a company that not only economically afloat but exceeds in profitability.